Nursing Competency of New Pediatric Nurses in the Post-COVID-19 - Cheunbun, Yodkhwan (Journal of The Royal Thai Army Nurses, 2023)
This academic article aims to present knowledge about new pediatric nursing competencies after COVID-19, consisting of pediatric nursing competencies in the transition era. Pediatric Nursing for COVID-19 Patients Development of competency of future pediatric nurses Necessary competencies of pediatric nurses in the COVID-19 era The COVID-19 pandemic is a big challenge. Thailand has been affected by COVID-19. Which affects people’s lives in all aspects All sectors of society therefore help each other to seek coping and solving problems. They all agreed that they should learn and look ahead (Post COVID-19) and find opportunities in the crisis to restore normal life and improve their well-being. During the outbreak of COVID-19 in Thailand found Pediatric patients under 10 years of age were infected by 2.71% of all cases and the youngest infected was 1month. The workload increases simultaneously with manpower shortages As for pediatric nurses, they must be able to study or search for guidelines on nursing care for pediatric patients infected with COVID-19, as well as to prevent the spread of infection properly and efficiently. If pediatric nurses are knowledgeable and ready to work, it will help to have more confidence in taking care of pediatric patients. and able to face various situations Make decisions to solve problems and help young patients in a timely manner. Therefore, all child nurses must have sufficient knowledge and competence. Be able to adapt and learn the correct methods of infection prevention and spread. In conclusion, it can be concluded that the new pediatric nursing competency is a challenge that will enable child caregivers to manage COVID-19 effectively and gain acceptance from parents or guardians who care for their children in times of need. Families have to face this disease.